Towards a trans-epistemic society - Petitat, Andre (Technium Social Sciences Journal, 2021)
The article schematically presents four types of codes associated with four forms of intelligence of the living (genomic, sensorimotor, symbolic and digital). It is particularly interested in the feedback effects of each higher level on previous levels and the sustained trend towards externalization. The human species is now reshaping these various forms of intelligence. The boundaries between natural, cultural and technical are in the process of blurring. A trans-epistemic society is emerging, which expressly includes the full depth of its relations with the biosphere.